Tuberculosis in Tropical Areas and Immigrants - Zammarchi, Lorenzo (Università Cattolica del Sacro Cuore, 2014)
About 95% of cases and 98% of deaths due to tuberculosis (TB) occur in tropical countries while, in temperate low incidence countries, a disproportionate portion of TB cases is diagnosed in immigrants. Urbanization, poverty, poor housing conditions and ventilation, poor nutritional status, low education level, the HIV co-epidemic, the growing impact of chronic conditions such as diabetes are the main determinants of the current TB epidemiology in tropical areas. TB care in these contests is complicated by several barriers such as geographical accessibility, educational, cultural, sociopsychological and gender issues. High quality microbiological and radiological facilities are not widely available, and erratic supply of anti-TB drugs may affect tropical areas from time to time. Nevertheless in recent years, TB control programs reached major achievements in tropical countries as demonstrated by several indicators. Migrants have a high risk of acquire TB before migration. Moreover, after migration, they are exposed to additional risk factors for acquiring or reactivating TB infection, such as poverty, stressful living conditions, social inequalities, overcrowded housing, malnutrition, substance abuse, and limited access to health care. TB mass screening programs for migrants have been implemented in low endemic countries but present several limitations. Screening programs should not represent a stand-alone intervention, but a component of a wider approach integrated with other healthcare activities to ensure the health of migrants.